Fungal alkaline proteases and their potential applications in different industries - Pawar, Kadambari Subhash; Singh, Paras Nath; Singh, Sanjay Kumar (Frontiers in Microbiology, 2023)
The consumption of various enzymes in industrial applications around the world has increased immensely. Nowadays, industries are more focused on incorporating microbial enzymes in multiple processes to avoid the hazardous effects of chemicals. Among these commercially exploited enzymes, proteases are the most abundantly used enzymes in different industries. Numerous bacterial alkaline proteases have been studied widely and are commercially available; however, fungi exhibit a broader variety of proteases than bacteria. Additionally, since fungi are often recognized as generally regarded as safe (GRAS), using them as enzyme producers is safer than using bacteria. Fungal alkaline proteases are appealing models for industrial use because of their distinct spectrum of action and enormous diversity in terms of being active under alkaline range of pH. Unlike bacteria, fungi are less studied for alkaline protease production. Moreover, group of fungi growing at alkaline pH has remained unexplored for their capability for the production of commercially valuable products that are stable at alkaline pH. The current review focuses on the detailed classification of proteases, the production of alkaline proteases from different fungi by fermentation (submerged and solid–state), and their potential applications in detergent, leather, food, pharmaceutical industries along with their important role in silk degumming, waste management and silver recovery processes. Furthermore, the promising role of alkali–tolerant and alkaliphilic fungi in enzyme production has been discussed briefly. This will highlight the need for more research on fungi growing at alkaline pH and their biotechnological potential.